1983 թ. մայիսի 17-ի լիբանանաիսրայելական համաձայնագիրը լիբանանյան հակամարտության միջազգայնացման համատեքստում - Հարությունյան, Լիլիթ («Զանգակ - 97»)
The developments that passed in Lebanon in the beginnig of 1980's - the Israeli Intervention in 1982, the entrance of the Multinational Forces, the subscription of the Lebanese-Israeli Peace Treaty, as the result the deepenning of the Lebanese crisis was greatly conditioned also with the deepenning of contradictions between Great States and their Middle East allies in the context of Cold War.
Keywords: Պատմություն; Քաղաքականություն